Geophysical issues and challenges in Malay and adjacent basins from an E&P perspective - GHOSH, DEVA (Society of Exploration Geophysicists, 2010)
Malay Basin, a northward-trending pull-apart extensional rift basin, formed during the late Eocene-early Oligocene and then underwent thermal subsidence and sedimentation during the early Miocene. Reorientation of regional stress fields during the mid-Miocene caused structural inversion resulting in east-west anticlines and half grabens.The basin (Figure 1) is 500 km long and 200 km wide and slightly asymmetrical with the gentler side showing greater hydrocarbon potential. This is one of the deepest basins (12 km at center) in this part of SE Asia and an excellent kitchen with rich source rocks. Two effective petroleum systems have been identified: the mid-Miocene coaly shales of terrestrial origin, generally gas-prone, to the north and the lacustrine shales of Oligocene-Miocene age. The Oligocene sediments are of terrestrial origin; the Miocene sediments were deposited in coastal-to-shallow marine environments. Stratigraphically, Malay Basin is subdivided into groups starting from the youngest (A) to the oldest (M). Exploration currently focuses primarily on groups E–K (Figure 1). The lithology consists of a thinly layered sand-shale sequence of layer-cake configuration. Coal is found from E through the deeper groups but most prominently in group I in a lower coastal-plain setting. The other basins discussed in this paper are Sarawak (late Eocene to recent) and Sabah (mid-Miocene to recent). Sarawak Basin is part of the Sunda continental margin and shelf that structurally connects Peninsular Malaysia (PM) with Borneo. It is separated from Sabah Basin by a major structural feature, the West Baram Line, that isolates the carbonate shelf of Sarawak (Luconia) from the siliciclastics of the Baram delta and beyond. Tectonically, Sabah’s geology is complex with steep dips, growth faulting, and overthrusts. Stratigraphically,the Sarawak units are subdivided into cycles (Shell nomenclature) with cycle I/II being the oldest and VI/VIII being the youngest. Sabah’s stratigraphy is punctuated by tectonically controlled unconformities and the units are commonly named “stages.”